Dampak Atraumatic Care Pada Kepuasan Keluarga Pasien di Rumah Sakit - Jebul Suroso; Iis Fetianingsih; Eko Mardiyaningsih (Program Studi S1 Keperawatan Universitas Ngudi Waluyo, 2018)
Atraumatic care is a specific therapeutic treatment performed by nurses through intervention by eliminating or minimizing psychological and physical stress suffered by children and family in health service system. The objective of this study is to give an overview on the effects of atraumatic care on parentsâ€™ satisfaction while children are being hospitalized. This study used correlational descriptive method with cross sectional approach. The 60 respondents as samples were selected with random sampling technique. The data analysys used chi square. The results showed autramatic care was performed in â€œGoodâ€ category with 60%. The parents satisfaction was on â€œSatisfiedâ€ level with 53,3%. Atraumatic care is proven to be correlated with familyâ€™s satisfaction with p value 0,045 < Î± 0,05. As a conclusion, there is an effect given by atraumatic care on family/ parentsâ€™ satisfaction while children are being hospitalized.